Using agent based modeling to assess the effect of transport policies on the use of active transportation in Bogotá (2018)
Environmental and social effect on walking behavior have received attention in recent years because the potential on assess transport policies. There is evidence that physical inactivity (PI) is now identified as the fourth leading risk factor for global mortality. This is an opportunity to develop models and policies for the very purpose of increasing physical activity (PA) on population. We found on literature that growth of the Bus Rapid Transit (BRT) causes positive effects on walking, other findings stablish that social interaction promotes eco-commuting. We develop an agent-based model (ABM) to assess the effect of some policies on the use of active transportation in Bogotá. In the ABM agents are assigned a household, workplace, and socioeconomic status (SES) and consequently the income for transportation. Each agent based on an utility function decide between the available modes of transport as walking, bicycling, bus, Transmilenio (TM), taxi or car taking into account the available resources, time to reach destination and service satisfaction per mode of transportation that is updated each day. The ABM consider also social interaction between agents in a social network, which experience unsafe events during commuting. The results indicates that it is possible to promote active commuting and so physical activity on individuals under certain conditions.